From Artificial to Emotional Intelligence: Integrating Five Types of Intelligence to Achieve Organizational Excellence - Chaojie Wang; Fred Hoffman; Alvi Lim; Jin Kwon (International School for Social and Business Studies, 2019)
Decision Support Systems have significance, as today firms turn to big data, machine learning, and artificial intelligence to guide strategy development and improve organizational performance. However, technology is not enough; human intelligence is necessary. This paper introduces Artificial Intelligence to the Emotional Intelligence Model, which blends technology and humanity to support strategic decision-making. Such a model builds on the DataInformation-Knowledge-Wisdom hierarchy and knowledge management to integrate five types of intelligence. The consumer electronics retail giant Best Buy is used as a case to illustrate the relevance of the model. The presented framework provides a powerful, mental model to support organizational strategists and business executives.